Improving evidence based cardiac care and policy implementation over the patient journey: the potential of coronary heart disease registers. Issue 9 (15th August 2005) - Clark, A M; Findlay, I N
Abstract : Coronary heart disease registers offer considerable potential for providing increased support for practitioners, facilitating improvements in patient care, and allowing efficient monitoring of care provision and outcomes